Answer:
There is only one solution and the solution is (0,4).
Step-by-step explanation:
The given system has equations;
![y=-2x+4](https://tex.z-dn.net/?f=y%3D-2x%2B4)
and
![y=x^2-2x+4](https://tex.z-dn.net/?f=y%3Dx%5E2-2x%2B4)
We equate the two equations to determine their point of intersection;
![x^2-2x+4=-2x+4](https://tex.z-dn.net/?f=x%5E2-2x%2B4%3D-2x%2B4)
![\Rightarrow x^2-2x+2x+4-4=0](https://tex.z-dn.net/?f=%5CRightarrow%20x%5E2-2x%2B2x%2B4-4%3D0)
![\Rightarrow x^2=0](https://tex.z-dn.net/?f=%5CRightarrow%20x%5E2%3D0)
![\Rightarrow x=0](https://tex.z-dn.net/?f=%5CRightarrow%20x%3D0)
We put x=0 into the first equation to get;
![y=-2(0)+4=4](https://tex.z-dn.net/?f=y%3D-2%280%29%2B4%3D4)
There is only one solution and the solution is (0,4).